A preparation method of a wide temperature range high capacity cascade aqueous zinc-iodine battery and an aqueous zinc-iodine battery

By using bromine-rich polycationic hydrogel electrolyte and iodine composite positive electrode in aqueous zinc-iodine batteries and combining zinc negative electrodes, the problems of low energy density and insufficient cycle stability of aqueous zinc-iodine batteries are solved, and a battery with high capacity and excellent cycle performance in a wide temperature range is achieved.

CN119340510BActive Publication Date: 2025-03-21ANHUI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411874142.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The energy density of existing water-based zinc-iodine batteries is not high, and there are limitations in temperature changes and cycle stability.

Method used

The raw materials such as zinc perchlorate, bacterial cellulose, acrylamide and 1-vinyl-3-butylimidazole bromine salt were used to prepare bromine-rich polycationic hydrogel electrolyte through polymerization, and used it as an electrolyte and a separator, combined with the positive electrode of the iodine composite material and the negative electrode of the zinc, and assembled into an aqueous zinc-iodine battery.

Benefits of technology

In a wide temperature range from -50°C to 50°C, the battery exhibits extremely high specific capacity and excellent cycling performance, with a specific capacity reaching 630mAh/g, and a significant improvement in cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340510B_ABST
    Figure CN119340510B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method of a wide temperature range high-capacity cascade aqueous zinc-iodine battery and an aqueous zinc-iodine battery, which belongs to the technical field of aqueous zinc-ion batteries. The preparation method comprises: dissolving zinc perchlorate, bacterial cellulose, acrylamide, 1-vinyl-3-butylimidazolium bromide, a cross-linking agent and an initiator in water to obtain a mixed solution; the mixed solution is polymerized at 60°C to 80°C to obtain a bromine-rich polycationic hydrogel electrolyte; an iodine composite material is used as a positive electrode, metallic zinc is used as a negative electrode, and the bromine-rich polycationic hydrogel electrolyte is used as an electrolyte to assemble an aqueous zinc-iodine battery. The aqueous zinc-iodine battery prepared by the method has extremely high specific capacity and excellent cycle performance in a wide temperature range of ‑50°C to 50°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and particularly relates to a preparation method of a wide temperature range high-capacity cascade aqueous zinc-iodine battery and an aqueous zinc-iodine battery. Background Art

[0002] Compared with traditional alkali metal secondary batteries (lithium ion, sodium ion batteries, etc.), zinc iodine batteries using water as electrolyte have the advantages of low cost, high safety, non-toxicity and easy recycling, and are more advantageous in large-scale energy storage systems. - / I2 Two-electron reaction Traditional aqueous zinc-iodine batteries only provide a theoretical capacity of 211mAh / g, which seriously limits the energy density of aqueous zinc-iodine batteries. In addition, in the process of improving the energy density of batteries, the aqueous zinc-iodine battery technology reported today is difficult to take into account the side reactions on the zinc negative electrode side and the application restrictions of temperature on aqueous batteries, which greatly limits the cycle stability of zinc-iodine batteries. Therefore, it is urgent to develop a wide temperature range and high-capacity aqueous zinc-iodine battery. Summary of the invention

[0003] In order to solve the problem of low energy density of existing aqueous zinc-iodine batteries, the present invention provides a method for preparing a wide-temperature range high-capacity cascade aqueous zinc-iodine battery. The aqueous zinc-iodine battery prepared by the method has extremely high specific capacity and excellent cycle performance in a wide temperature range of -50°C to 50°C.

[0004] The present invention also provides a wide temperature range and high capacity cascade aqueous zinc-iodine battery.

[0005] The present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery, the preparation method comprising:

[0007] Dissolving zinc perchlorate, bacterial cellulose, acrylamide, 1-vinyl-3-butylimidazolium bromide, a crosslinking agent and an initiator in water to obtain a mixed solution;

[0008] The mixed solution is polymerized at 60°C to 80°C to obtain a bromine-rich polycationic hydrogel electrolyte;

[0009] An aqueous zinc-iodine battery is assembled using the iodine composite material as the positive electrode, metal zinc as the negative electrode, and the bromine-rich polycationic hydrogel electrolyte as the electrolyte.

[0010] Furthermore, in the mixed solution, the concentration of zinc perchlorate is 1 to 3 mol / L, the concentration of bacterial cellulose is 0.1 to 0.5 wt%, the concentration of acrylamide is 1 to 3 mol / L, the concentration of 1-vinyl-3-butylimidazolium bromide is 0.1 to 1 mol / L, the concentration of the crosslinking agent is 0.001 to 0.004 mol / L, and the concentration of the initiator is 0.010 to 0.052 mol / L.

[0011] Furthermore, the cross-linking agent includes N,N-methylenebisacrylamide, and the initiator includes ammonium persulfate.

[0012] Further, the mixed solution is polymerized at 60°C to 80°C to obtain a bromine-rich polycationic hydrogel electrolyte, which specifically includes:

[0013] The mixed solution is polymerized at 60°C to 80°C for 8 to 12 hours to obtain a bromine-rich polycationic hydrogel electrolyte.

[0014] Furthermore, the positive electrode is prepared by the following method:

[0015] dispersing iodine, activated carbon, bacterial cellulose and carbon nanotubes in water to obtain a dispersion;

[0016] The dispersion is stirred, filtered, and then dried to obtain the positive electrode.

[0017] Furthermore, the mass ratio of the iodine, the activated carbon, the bacterial cellulose and the carbon nanotubes is (2-4): (4-6): 1:1.

[0018] Further, the dispersion is stirred for a certain period of time, filtered, and then dried to obtain the positive electrode, which specifically includes:

[0019] The dispersion is stirred for 24±6 h, filtered, and then dried to obtain the positive electrode.

[0020] Furthermore, the negative electrode comprises a zinc sheet or a zinc foil with a thickness of 20 to 100 μm.

[0021] Based on the same inventive concept, the present invention provides a wide temperature range high capacity cascade aqueous zinc-iodine battery, and the aqueous zinc-iodine battery is prepared by the above-mentioned preparation method of a wide temperature range high capacity cascade aqueous zinc-iodine battery.

[0022] Alternatively, the present invention provides a wide temperature range high-capacity cascade aqueous zinc-iodine battery, which is assembled in the order of positive electrode shell-gasket-positive electrode-electrolyte-negative electrode-negative electrode shell, and the positive electrode, electrolyte and negative electrode in the aqueous zinc-iodine battery are respectively the same as the positive electrode, the electrolyte and the negative electrode defined or prepared by the above-mentioned preparation method of a wide temperature range high-capacity cascade aqueous zinc-iodine battery.

[0023] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0024] 1. The present invention discloses a method for preparing a wide temperature range high-capacity cascade aqueous zinc-iodine battery. The method uses zinc perchlorate, bacterial cellulose, acrylamide and 1-vinyl-3-butylimidazolium bromide as raw materials, obtains a bromine-rich polycationic hydrogel electrolyte by a one-step polymerization method under the action of a crosslinking agent and an initiator, successfully introduces bromine elements and a polymer cation skeleton into the electrolyte of the aqueous zinc-iodine battery, and activates a stable four-electron I - / I2 / I + Simultaneous cascade iodine conversion reaction Br - / Br 0 The zinc-iodine battery prepared by the conversion reaction exhibits good electrochemical performance in a wide temperature range of -50°C to 50°C, and has extremely high specific capacity and excellent cycle performance.

[0025] 2. The present invention discloses a wide temperature range high capacity cascade aqueous zinc-iodine battery, which is composed of a battery shell, a positive electrode, a negative electrode, and a gel electrolyte (which can also serve as a separator), wherein the positive electrode is a composite material of iodine and activated carbon, the negative electrode is a zinc sheet, and the gel electrolyte is a bromine-rich polycationic hydrogel electrolyte. The aqueous zinc-iodine battery introduces bromine into the aqueous zinc-iodine battery electrolyte, successfully activating the I-based - / I2 / I + Four-electron iodine conversion reaction and cascade of Br - / Br 0 The conversion reaction has a specific capacity of 630 mAh / g based on the mass of iodine. The present invention introduces a polymer cation skeleton into an aqueous zinc-iodine battery, and significantly improves the reversibility of the above-mentioned cascade reaction through the stabilizing effect of cations on polyiodides, thereby improving the cycle stability of the battery. In addition, the water molecules in the bromine-rich polycationic hydrogel electrolyte limit the activity of the water molecules by forming hydrogen bonds with the anions in the zinc salt and the hydroxyl and amide groups in the polymer cation skeleton, thereby inhibiting the growth of byproducts on the surface of the zinc negative electrode and zinc dendrites, thereby achieving uniform zinc deposition. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 It is a comparison diagram of the constant current charge and discharge curves of the zinc-iodine full batteries assembled in Example 1 and Comparative Examples 2 and 3.

[0028] Figure 2 This is a comparison chart of the long cycles of the zinc-iodine full batteries assembled in Example 1 and Comparative Examples 2 and 3.

[0029] Figure 3 It is a comparison diagram of the constant current charge and discharge curves of the zinc-iodine full batteries assembled in Examples 1, 2, and 3.

[0030] Figure 4 The differential scanning calorimetry curves of the electrolytes in Example 1 and Comparative Examples 1 and 2 are shown.

[0031] Figure 5 These are optical photographs of the electrolytes in Example 1 and Comparative Examples 1 and 2 after being placed at -50°C for 12 hours.

[0032] Figure 6 1 and 2 are tensile stress curves of the electrolytes prepared in Example 1 and Comparative Example 1.

[0033] Figure 7 This is a scan of the surface morphology of the zinc negative electrode in Comparative Example 2 after contact with the electrolyte for 7 days.

[0034] Figure 8 This is a scan of the surface morphology of the zinc negative electrode in Example 1 after being in contact with the electrolyte for 7 days.

[0035] Fig. 9 This is a scan of the zinc sheet surface after the Zn-Zn symmetric battery assembled with the electrolyte in Comparative Example 2 was cycled 20 times.

[0036] Fig.10 This is a scan of the zinc sheet surface after the Zn-Zn symmetric battery assembled with the electrolyte in Example 1 was cycled 20 times.

[0037] Fig.11 This is a comparison chart of the long cycle of Zn-Zn symmetric batteries assembled with electrolytes in Example 1 and Comparative Examples 1 and 2.

[0038] Fig.12 This is the rate performance of the zinc-iodine full battery assembled in Example 1 at -50°C.

[0039] Fig.13The long cycle performance of the zinc-iodine full battery assembled in Example 1 at -50°C.

[0040] Fig.14 This is the long cycle performance of the zinc-iodine full battery assembled in Example 1 at 50°C. DETAILED DESCRIPTION

[0041] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0042] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0044] The technical principles of the present invention are as follows:

[0045] The present invention provides a wide temperature range high capacity cascade aqueous zinc-iodine battery. The positive electrode of the aqueous zinc-iodine battery is a composite material of iodine and activated carbon, the negative electrode is a zinc sheet, and a bromine-rich polycationic hydrogel electrolyte is used as an electrolyte and a diaphragm. The aqueous zinc-iodine battery introduces bromine into the aqueous zinc-iodine battery electrolyte, which can form an interhalogen compound IBr2 with the iodine positive electrode. - , thereby activating the four-electron iodine conversion reaction I - / I2 / I + Based on this four-electron reaction, the specific capacity of the zinc-iodine battery has been significantly improved compared with the traditional two-electron reaction, and it can also cascade Br - / Br 0 Conversion reaction, activation of IBr2 - Br - The conversion to a higher valence state and the realization of a series reaction of two halogens in the same battery further increase the capacity of the zinc-iodine battery. Based on the mass of iodine, the specific capacity reaches 630 mAh / g.

[0046] The inventors found that in aqueous electrolytes, I + Ions are very susceptible to hydrolysis, requiring high concentrations of electrolytes and high concentrations of bromine to achieve I +Activation and stabilization of ions, however, high concentration electrolytes will bring high economic costs, and leakage of acidic electrolytes will also bring a series of safety hazards. In addition, it is also necessary to take into account the side reactions on the zinc negative electrode side and the application limitations of temperature on aqueous batteries. The present invention introduces a polymer cationic skeleton into an aqueous zinc-iodine battery, which effectively solves the above problems. Through the stabilizing effect of cations on polyiodides, the reversibility of the above-mentioned cascade reaction is significantly improved, and the cycle stability of the battery is improved. In addition, the water molecules in the bromine-rich polycationic hydrogel electrolyte limit the activity of water molecules by forming hydrogen bonds with the anions in the zinc salt and the hydroxyl and amide groups in the polymer cationic skeleton, thereby inhibiting the growth of byproducts on the surface of the zinc negative electrode and zinc dendrites, thereby achieving uniform zinc deposition, so that the battery still exhibits a high specific capacity and excellent cycle stability at extreme temperatures.

[0047] The present invention provides a method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery, the preparation method comprising:

[0048] S1. dissolving zinc perchlorate, bacterial cellulose, acrylamide, 1-vinyl-3-butylimidazolium bromide, a crosslinking agent and an initiator in water to obtain a mixed solution;

[0049] S2. The mixed solution is polymerized at 60°C to 80°C to obtain a bromine-rich polycationic hydrogel electrolyte;

[0050] S3. An aqueous zinc-iodine battery is assembled using the iodine composite material as the positive electrode, the metallic zinc as the negative electrode, and the bromine-rich polycationic hydrogel electrolyte as the electrolyte.

[0051] In the present invention, the advantages of using zinc perchlorate, bacterial cellulose, acrylamide, and 1-vinyl-3-butylimidazolium bromide as raw materials to prepare the hydrogel electrolyte are: (1) the zinc perchlorate in the hydrogel forms hydrogen bonds with the hydrophilic groups and water molecules in the gel, thereby lowering the freezing point of the electrolyte; (2) the addition of bacterial cellulose effectively improves the mechanical properties of the hydrogel electrolyte; (3) the bromine element provided by 1-vinyl-3-butylimidazolium bromide and -NR3 + Positively charged groups activate I - / I2 / I + Br - / Br 0 The cascade reaction also improves the reversibility of the reaction, thereby increasing the battery cycle life.

[0052] Wherein, in the mixed solution, the concentration of zinc perchlorate is 1-3 mol / L, the concentration of bacterial cellulose is 0.1-0.5 wt%, the concentration of acrylamide is 1-3 mol / L, the concentration of 1-vinyl-3-butylimidazolium bromide is 0.1-1 mol / L, the concentration of the cross-linking agent is 0.001-0.004 mol / L, and the concentration of the initiator is 0.010-0.052 mol / L.

[0053] In the present invention, the advantages of using zinc perchlorate, bacterial cellulose, acrylamide, 1-vinyl-3-butylimidazolium bromide, crosslinking agent and initiator in the above concentration range are as follows: (1) high concentration of zinc perchlorate can ensure that the hydrogel electrolyte has a lower freezing point and higher ionic conductivity; (2) the concentrations of the above bacterial cellulose and acrylamide ensure that the hydrogel has a reasonable pore size distribution, which improves the rapid passage of the migration of the aqueous electrolyte; (3) low concentration of 1-vinyl-3-butylimidazolium bromide effectively reduces the halogen concentration in the electrolyte, thereby alleviating the corrosion of the halogen on the zinc negative electrode and the metal battery components.

[0054] Furthermore, the cross-linking agent includes N,N-methylenebisacrylamide, and the initiator includes ammonium persulfate.

[0055] In the present invention, the crosslinking agent is N,N-methylenebisacrylamide, and the initiator is ammonium persulfate. The advantages are that the crosslinking agent and initiator used are widely used and low in price, and the polymerization reaction is ensured to proceed quickly.

[0056] Step S2 specifically includes:

[0057] The mixed solution is polymerized at 60°C to 80°C for 8 to 12 hours to obtain a bromine-rich polycationic hydrogel electrolyte.

[0058] In the present invention, the polymerization temperature of the mixed solution is 60°C to 80°C, the reaction conditions are mild, and the operation is easy. Too high a polymerization temperature causes water loss in the hydrogel electrolyte, and too low a temperature causes an incomplete polymerization reaction.

[0059] Furthermore, the positive electrode is prepared by the following method:

[0060] dispersing iodine, activated carbon, bacterial cellulose and carbon nanotubes in water to obtain a dispersion;

[0061] The dispersion is stirred for a certain period of time, filtered, and then dried to obtain the positive electrode.

[0062] Wherein, the mass ratio of the iodine, the activated carbon, the bacterial cellulose and the carbon nanotubes is (2-4): (4-6): 1:1;

[0063] The dispersion is stirred for 24±6 h, filtered, and then dried to obtain the positive electrode.

[0064] In the present invention, the positive electrode is prepared using iodine, activated carbon, bacterial cellulose and carbon nanotubes as raw materials, which can give the positive electrode an efficient conductive network and ensure the rapid progress of the positive electrode conversion reaction; wherein the mass ratio of iodine, activated carbon, bacterial cellulose and carbon nanotubes is (2-4): (4-6): 1:1, which has the advantage that the positive electrode capacity is fully released; the purpose of stirring the dispersion for 24±6 h is to ensure that the activated carbon can fully adsorb the iodine active substance.

[0065] The following will describe in detail a method for preparing a wide temperature range high-capacity cascade aqueous zinc-iodine battery and an aqueous zinc-iodine battery in combination with examples and experimental data.

[0066] The battery performance tests in the following embodiments and comparative examples all adopted the Xinwei battery testing system.

[0067] The assembly method of the Zn-Zn symmetrical battery includes: placing two polished zinc sheets at the positive and negative electrodes respectively, using the electrolyte prepared in the following embodiments and comparative examples, using the prepared gel electrolyte or glass fiber as a separator, and assembling into a 2032 button battery.

[0068] The assembling method of the zinc-iodine full battery comprises: uniformly dispersing elemental iodine, activated carbon, bacterial cellulose and carbon nanotubes in an aqueous solution according to a mass ratio of 2:6:1:1 to obtain a mixed solution, stirring at room temperature for 24 hours, filtering and drying the mixed solution to prepare a positive electrode, using the electrolyte prepared in the following embodiments and comparative examples, and using the gel electrolyte or glass fiber prepared in the following embodiments and comparative examples as a separator, and a zinc sheet as a negative electrode (with a thickness of 100 mm), to assemble a 2032 button battery.

[0069] Example 1

[0070] The present embodiment provides a method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery, which specifically includes:

[0071] Step 1: Weigh 3.724 g zinc perchlorate hexahydrate, 2 mL 0.8 wt% bacterial cellulose solution, 0.710 g acrylamide, 1.156 g 1-vinyl-3-butylimidazolium bromide, 0.003 g N,N-methylenebisacrylamide, and 0.03 g ammonium persulfate in a beaker, add 2 mL deionized water, and stir at room temperature for 60 min to obtain 5 mL of a clear mixed solution.

[0072] Step 2: Pour the above mixed solution into a polytetrafluoroethylene mold with a depth of 200 μm, and polymerize it at 60°C for 12 hours to obtain a hydrogel electrolyte named BAVBr.

[0073] Step 3: The gel electrolyte prepared in step 2 is used as an electrolyte and a separator, and is assembled with the positive electrode and the negative electrode in the order of positive electrode shell-gasket-positive electrode-hydrogel electrolyte (also serving as a separator)-negative electrode-negative electrode shell to prepare a 2032 button zinc-iodine battery.

[0074] Example 2

[0075] The present embodiment provides a method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery, which specifically includes:

[0076] Step 1: Weigh 3.724 g zinc perchlorate hexahydrate, 2 mL 0.8 wt% bacterial cellulose solution, 0.710 g acrylamide, 0.116 g 1-vinyl-3-butylimidazolium bromide, 0.0015 g N,N-methylenebisacrylamide, and 0.015 g ammonium persulfate in a beaker, add 2 mL deionized water, and stir at room temperature for 60 min to obtain a clear mixed solution.

[0077] Step 2: Pour the above mixed solution into a polytetrafluoroethylene mold with a depth of 200 μm, and polymerize it at 60°C for 12 hours to obtain a hydrogel electrolyte named BAVBr-0.1.

[0078] Step 3: The gel electrolyte prepared in step 2 is used as an electrolyte and a separator, and is assembled with the positive electrode and the negative electrode in the order of positive electrode shell-gasket-positive electrode-hydrogel electrolyte (also serving as a separator)-negative electrode-negative electrode shell to prepare a 2032 button zinc-iodine battery.

[0079] Example 3

[0080] The present embodiment provides a method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery, which specifically includes:

[0081] Step 1: Weigh 3.724 g zinc perchlorate hexahydrate, 2 mL 0.8 wt% bacterial cellulose solution, 0.710 g acrylamide, 0.578 g 1-vinyl-3-butylimidazolium bromide, 0.0025 g N,N-methylenebisacrylamide, and 0.025 g ammonium persulfate in a beaker, add 2 mL deionized water, and stir at room temperature for 60 min to obtain a clear mixed solution.

[0082] Step 2: Pour the above mixed solution into a polytetrafluoroethylene mold with a depth of 200 μm, and polymerize it at 60°C for 12 hours to obtain a hydrogel electrolyte named BAVBr-0.5.

[0083] Step 3: The gel electrolyte prepared in step 2 is used as an electrolyte and a separator, and is assembled with the positive electrode and the negative electrode in the order of positive electrode shell-gasket-positive electrode-hydrogel electrolyte (also serving as a separator)-negative electrode-negative electrode shell to prepare a 2032 button zinc-iodine battery.

[0084] Comparative Example 1

[0085] The present embodiment provides a method for preparing an aqueous zinc-iodine battery, which specifically includes:

[0086] Step 1: Weigh 2 mL of 0.8 wt% bacterial cellulose solution, 0.710 g of acrylamide, 1.156 g of 1-vinyl-3-butylimidazolium bromide, 0.003 g of N,N-methylenebisacrylamide, and 0.03 g of ammonium persulfate in a beaker, add 2 mL of deionized water, and stir at room temperature for 60 min to obtain a clear mixed solution.

[0087] Step 2: Pour the mixed solution into a polytetrafluoroethylene mold with a depth of 200 μm, and polymerize at 60° C. for 12 h to obtain a zinc-free salt water gel.

[0088] Step 3: Soak the above zinc-free salt water gel in a 2M zinc perchlorate aqueous solution for 24 h to obtain a hydrogel electrolyte named BAVBr-Soaking.

[0089] Step 4: The gel electrolyte prepared in step 3 is used as an electrolyte and a separator, and is assembled with the positive electrode and the negative electrode in the order of positive electrode shell-gasket-positive electrode-hydrogel electrolyte (also serving as a separator)-negative electrode-negative electrode shell to prepare a 2032 button zinc-iodine battery.

[0090] Comparative Example 2

[0091] The present embodiment provides a method for preparing an aqueous zinc-iodine battery, which specifically includes:

[0092] Step 1: Weigh 3.724 g of zinc perchlorate hexahydrate and dissolve it in 4.5 mL of deionized water to obtain a liquid 2 M zinc perchlorate electrolyte named Zn(ClO4)2.

[0093] Step 2: Use the Zn(ClO4)2 prepared in step 1 as the electrolyte and the glass fiber as the separator, and assemble the positive electrode and the negative electrode in the order of positive electrode shell-gasket-positive electrode-Zn(ClO4)2-glass fiber separator-negative electrode-negative electrode shell to prepare a 2032 button zinc-iodine battery.

[0094] Comparative Example 3

[0095] The present embodiment provides a method for preparing an aqueous zinc-iodine battery, which specifically includes:

[0096] Step 1: Weigh 3.724 g zinc perchlorate hexahydrate and 0.563 g zinc bromide and dissolve them in 4.5 mL deionized water to obtain a liquid 2M zinc perchlorate + 0.5M zinc bromide electrolyte, named Zn(ClO4)2+ZnBr2.

[0097] Step 2: Use the Zn(ClO4)2+ZnBr2 prepared in step 1 as electrolyte and glass fiber as separator, and assemble with the positive electrode and negative electrode in the order of positive electrode shell-gasket-positive electrode-Zn(ClO4)2+ZnBr2-glass fiber separator-negative electrode-negative electrode shell to prepare a 2032 button zinc-iodine battery.

[0098] Figure 1 The constant current charge and discharge curves of the zinc-iodine full battery assembled using the electrolytes of Example 1 and Comparative Examples 2 and 3 in the voltage range of 0.5-1.8V are shown. As can be seen from the figure, at a current density of 1A / g, the zinc-iodine battery using Comparative Example 2 only releases a specific capacity of 248mAh / g. Although the zinc-iodine battery using Comparative Example 3 releases an ultra-high capacity of 664mAh / g, its coulombic efficiency is only 86%, and the energy utilization rate is low. While the zinc-iodine battery using Example 1 releases a high capacity of 630mAh / g, the coulombic efficiency is as high as 97%. This shows that the bromine-rich polycationic hydrogel electrolyte described in the present invention can cause a multi-electron reaction to occur at the positive electrode, thereby providing a higher specific capacity.

[0099] Figure 2 The cycling performance of zinc-iodine batteries assembled using the electrolytes of Example 1 and Comparative Examples 2 and 3 at a current density of 1A / g is compared. As can be seen from the figure, although the bromine element in the electrolyte of Comparative Example 3 can stimulate the multi-electron reaction of iodine and the redox reaction of bromine, the intermediate product is extremely unstable in the electrolyte, and the battery fails after 160 cycles due to its low coulomb efficiency. On the contrary, in the gel electrolyte of Example 1, the multi-electron reaction of iodine and the reaction of bromine are stabilized by the cationic skeleton in the gel electrolyte, and the reversibility of the reaction is significantly improved. Therefore, the specific capacity of the full battery still maintains 91% of the initial capacity after 4000 cycles.

[0100] Figure 3 The figure is a comparison of the charge and discharge curves of the zinc-iodine battery assembled using the electrolytic electrolytes of Examples 1, 2, and 3 at a current density of 1A / g. As can be seen from the figure, Example 1 releases a specific capacity of 630mAh / g, which is the highest value among the three. Example 2 and Example 3 release specific capacities of 620mAh / g and 501mAh / g, respectively. This shows that the ratio of each component in Example 1 is optimal.

[0101] Figure 4The differential scanning cooling and heating curves of Example 1 of the present invention and Comparative Examples 1 and 2. It can be seen from the figure that compared with the traditional liquid electrolyte in Comparative Example 2 (freezing point of -34.2°C) and the gel electrolyte prepared by the immersion method in Comparative Example 1 (freezing point of -38.5°C), the freezing point of the gel electrolyte in Example 1 is as low as -61.9°C.

[0102] Figure 5 The optical photographs of the electrolytes in Example 1 of the present invention and Comparative Examples 1 and 2 after being placed at -50°C for 12 hours are shown in the figure. As can be seen from the figure, both Comparative Examples 1 and 2 are in a solid state, while Example 1 of the present invention still maintains a stretchable and flexible state at -50°C, further illustrating the excellent antifreeze performance of the electrolyte in Example 1.

[0103] Figure 6 The tensile stress curves of the electrolytes in Example 1 and Comparative Example 1 of the present invention are shown in FIG. As can be seen from the figure, the gel electrolyte in Comparative Example 1 breaks when the tensile stress is 54.3 kPa, and the tensile length is 198%. The tensile stress and length of the gel in Example 1 of the present invention are increased to 63 kPa and 246%, respectively.

[0104] Figure 7 , 8 The surface morphology scans of the electrolyte and the zinc negative electrode after 7 days of contact in Example 1 and Comparative Example 2 are shown respectively. Figure 7 It can be seen that after immersion for 7 days in Comparative Example 1, obvious block byproducts appeared on the surface of the zinc negative electrode, while Figure 8 The zinc surface in Example 1 still maintains a smooth morphology and structure, which indicates that the hydrogel electrolyte of the present invention can effectively inhibit the corrosion of the zinc negative electrode in the electrolyte.

[0105] Fig. 9 , 10 The following are scanned images of the zinc negative electrode surface of the Zn-Zn symmetrical battery assembled using Example 1 and Comparative Example 2 after 20 cycles. Fig. 9 It can be seen that the zinc negative electrode in Comparative Example 2 has obvious holes and loose flaky deposits on its surface after cycling. In contrast, the zinc negative electrode in Example 1 shows smooth and dense zinc deposits after cycling ( Fig.10 ), maintaining the stability of the structure. This shows that the hydrogel electrolyte of the present invention can effectively inhibit the side reactions and dendrite growth during the zinc negative electrode cycle.

[0106] Fig.11 The Zn-Zn symmetrical battery assembled using Example 1 and Comparative Example 1 and Comparative Example 2 was used at 1 mA / cm 2Comparison of long cycle performance under current density. The Zn-Zn symmetric battery using Comparative Examples 1 and 2 will have severe side reactions and dendrite growth problems during the cycle, and short circuits will occur after 1140h and 120h of cycling respectively. On the contrary, in the hydrogel electrolyte in Example 1, the cycle stability of the zinc symmetric battery is significantly improved. Specifically, the Zn-Zn symmetric battery based on Example 1 can be stably cycled for 3500h without obvious voltage hysteresis.

[0107] Fig.12 , 13 They are respectively the rate performance and long cycle performance (current density 0.5A / g) of the zinc-iodine full battery assembled using Example 1 at -50°C. As can be seen from the figure, the assembled zinc-iodine battery releases a specific capacity of 400mAh / g at an extremely low temperature of -50°C, and the specific capacity remains at 75% of the initial capacity when the current density increases 5 times, indicating that Example 1 still has excellent ion conductivity at low temperatures. At the same time, the zinc-iodine battery also exhibits excellent cycle stability. Specifically, after 1500 cycles at a current density of 0.5A / g, the capacity retention rate is 88%.

[0108] Fig.14 This is the long cycle performance of the zinc-iodine full battery assembled using Example 1 at a high temperature of 50°C. As can be seen from the figure, at a current density of 1A / g, the zinc-iodine full battery can be stably cycled 1000 times, with a residual specific capacity of 439mAh / g and a capacity retention rate of 71%. This shows that the hydrogel electrolyte of the present invention has great tolerance to high temperature environments.

[0109] In summary, the present invention provides a wide temperature range high capacity cascade aqueous zinc iodine battery and a preparation method thereof, and the introduction of bromine elements and cationic skeletons in the gel electrolyte activates and stabilizes the four-electron I - / I2 / I + The iodine conversion reaction cascades into Br - / Br 0 The prepared cascade aqueous zinc-iodine battery released an ultra-high specific capacity of 630mAh / g and excellent cycle stability, and the operating temperature of the battery was extended to -50℃ to 50℃. This is of great significance for the construction of high specific energy and wide temperature range aqueous zinc-iodine batteries.

[0110] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0111] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0112] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery, characterized in that: The preparation method comprises: Dissolving zinc perchlorate, bacterial cellulose, acrylamide, 1-vinyl-3-butylimidazolium bromide, a crosslinking agent and an initiator in water to obtain a mixed solution; The mixed solution is polymerized at 60° C. to 80° C. to obtain a bromine-rich polycationic hydrogel electrolyte; An aqueous zinc-iodine battery is assembled using an iodine composite material as a positive electrode, metal zinc as a negative electrode, and the bromine-rich polycationic hydrogel electrolyte as an electrolyte; in the mixed solution, the concentration of zinc perchlorate is 1 to 3 mol / L, the concentration of bacterial cellulose is 0.1 to 0.5 wt%, the concentration of acrylamide is 1 to 3 mol / L, the concentration of 1-vinyl-3-butylimidazolium bromide is 0.1 to 1 mol / L, the concentration of the crosslinking agent is 0.001 to 0.004 mol / L, and the concentration of the initiator is 0.010 to 0.052 mol / L; The cross-linking agent includes N,N-methylenebisacrylamide, and the initiator includes ammonium persulfate.

2. The method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery according to claim 1, characterized in that: The mixed solution is polymerized at 60° C. to 80° C. to obtain a bromine-rich polycationic hydrogel electrolyte, which specifically comprises: The mixed solution is polymerized at 60° C. to 80° C. for 8 to 12 hours to obtain a bromine-rich polycationic hydrogel electrolyte.

3. The method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery according to claim 1, characterized in that: The positive electrode is prepared by the following method: dispersing iodine, activated carbon, bacterial cellulose and carbon nanotubes in water to obtain a dispersion; The dispersion is stirred, filtered, and then dried to obtain the positive electrode.

4. The method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery according to claim 3, characterized in that: The mass ratio of the iodine, the activated carbon, the bacterial cellulose and the carbon nanotubes is (2-4):(4-6):1:

1.

5. The method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery according to claim 3, characterized in that: The dispersion is stirred for a certain period of time, filtered, and then dried to obtain the positive electrode, which specifically includes: The dispersion is stirred for 24±6 hours, filtered, and then dried to obtain the positive electrode.

6. The method for preparing a wide temperature range high capacity cascade aqueous zinc-iodine battery according to claim 1, characterized in that: The negative electrode comprises a zinc sheet or a zinc foil with a thickness of 20 to 100 μm.

7. A wide temperature range high capacity cascade aqueous zinc-iodine battery, characterized in that: The aqueous zinc-iodine battery is prepared by the preparation method of a wide temperature range high-capacity cascade aqueous zinc-iodine battery according to any one of claims 1 to 6.

8. A wide temperature range high capacity cascade aqueous zinc-iodine battery, characterized in that: The aqueous zinc-iodine battery is assembled in the order of positive electrode shell-gasket-positive electrode-electrolyte-negative electrode-negative electrode shell, and the positive electrode, electrolyte and negative electrode in the aqueous zinc-iodine battery are respectively the same as the positive electrode, the electrolyte and the negative electrode defined or prepared in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Aqueous zinc-double halogen battery based on multi-electron conversion reaction and electrolyte of aqueous zinc-double halogen battery

    CN114709494A